Design method and engineering application of shear wall with friction energy dissipation damper - Bin Dang; Tao Li; Sheliang Wang; Meng Zhan (Građevinar)
At present, the target of seismic strengthening is to gradually work towards the objective of being able to quickly restore function, and even replace function after an earthquake. In addition, the foot of reinforced concrete shear walls is easily damaged in shear wall structures. If a damper is set in this part, it can ensure the normal stiffness and energy consumption function of the shear wall, and it can be easily and conveniently replaced after an earthquake at a low cost, which is an important measure to realize recoverable functional cities. Therefore, a new type of friction energy dissipation damper has been designed. First, the components of the damper are described, and the design process, including the base placement area, bolt hole length, and initial slip force, is theoretically analysed. Then, on the basis of a shear wall test, SAP2000 is used to analyse and verify correctness of the model. Furthermore, the dampers are placed in the corner of the shear wall for remodelling. Considering different bolt hole lengths, the hysteretic performance, bearing capacity attenuation, stiffness degradation, and energy dissipation capacity of the model are compared and analysed. The results show that the friction energy dissipation damper can improve the energy dissipation capacity and delay the stiffness degradation and bearing capacity attenuation of the structure. This study provides a theoretical basis for a more detailed engineering design and application.